Quantitative proteomic analysis using a mouse model of Lewy body dementia induced by α-synuclein preformed fibrils injection - Akkentli, Fatih; Jang, In kyu; Choi, Yoonseop; Min, Young; Park, Jinhee; Jo, Heejin; Kim, Leoni; Mendpara, Aashi; Bains, Bikram; Yoo, Dongyoon; Xu, Jinchong; Na, Chan Hyun; et al. (Frontiers in Dementia, 2024)
The aggregation of α-synuclein in the nervous system leads to a class of neurodegenerative disorders termed α-synucleinopathies. A form of primary degenerative dementia called Lewy body dementia (LBD) often develops when these aggregations develop into intracellular inclusions called Lewy bodies (LB) and Lewy neurites (LN). Although high frequency of LBD are the leading cause of dementia after Alzheimer's disease (AD), limited information has been discovered about its pathological pathway or diagnostic criteria. In this report, we attempt to address such shortcomings via utilizing a proteomic approach to identify the proteome changes following intrastriatal injection of α-synuclein pre-formed fibril (α-syn PFF). Using mass spectrometry, we have identified a total of 179 proteins that were either up-or down-regulated at different time points, with the four proteins -TPP3, RAB10, CAMK2A, and DYNLL1, displaying the most significant changes throughout the timeframe. Through further examining the modulated proteins with network-based enrichment analyses, we have found that 1) the most significantly associated neurodegenerative pathways were Parkinson's (pV = 3.0e-16) and Huntington's (pV = 1.9e-15) disease, and 2) the majority of molecular functions specific to the pathology only appeared at later time points. While these results do not expose a conclusive biomarker for LBD, they suggest a framework that is potentially applicable to diagnose and differentiate LBD pathology from other forms of dementia by focusing on the cortical proteome changes which occur in a later time span.